Influence of level of grain supplementation on the performance of intensive-early stocked steers - R.C. Cochran; E.S. Vanzant; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1989)
Two levels of sorghum grain supplementation (2 or 4 lb/day) for"¢steers in an intensive-early stocking program tended to increase average daily gain in direct proportion to increasing supplement level (2.7 and 2.9 lb/day. respectively, compared to 2.5 lb with no supplement). Similarly, grass remaining in the pastures after the cattle were removed on July 15, and at the end of the growing season on October 1, was greater when cattle were supplemented.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Grain supplementation; Stocker steers; Performance